2010
DOI: 10.1089/met.2009.0037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome in a Rural Community in Nigeria

Abstract: These results from a representative sample of the Nigerian rural population show a high prevalence of metabolic syndrome. The large number of Nigerians with the metabolic syndrome may have important implications for the health-care sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
36
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 23 publications
15
36
1
Order By: Relevance
“…40,41 Hypertension was found in 15.2% of the participants with no difference between the men and the women. Although the prevalence was lower than what Oladapo et al 16 reported, this rate was high considering the population studied and the age-adjusted National prevalence of 9.3% documented earlier. 42 The rising prevalence could also be due to the epidemiological transition that Nigeria is undergoing currently.…”
contrasting
confidence: 62%
See 2 more Smart Citations
“…40,41 Hypertension was found in 15.2% of the participants with no difference between the men and the women. Although the prevalence was lower than what Oladapo et al 16 reported, this rate was high considering the population studied and the age-adjusted National prevalence of 9.3% documented earlier. 42 The rising prevalence could also be due to the epidemiological transition that Nigeria is undergoing currently.…”
contrasting
confidence: 62%
“…Nigerian studies have estimated the point prevalence of MS to be between 2.4% -26.4%, with a higher rate among women in the general populace. [15][16][17][18][19] The prevalence was also higher in the urban compared to the rural areas. 17,[18][19][20] Among patients with type 2 diabetes, prevalence of MS ranged between 59.1%-87.1%, [21][22][23][24] while in patients with hypertension, the prevalence ranged between 24.7%-40.74%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study however, most of the prediabetic subjects had high abdominal obesity, which is in consonance with the studies that showed that the reason for the high prevalence of prediabetes is overweight and obesity, which may be due to the presence of insulin resistance and toxicity to beta cells due to the high level of free fatty acids in obese individuals [24,25]. In this study, SBP and DBP were higher in prediabetes compared with the control individual, which is an indication that they are predisposed to hypertension or prehypertension.…”
Section: Discussionsupporting
confidence: 91%
“…Watts (1983) referred to them as indigenous towns. In the context of Nigeria, such places are rural towns (Anong and Dipeolu, 1983;Okafor, 1991;Okafor and Okunji, 1996;Adegoke et al, 2010). Voss (2008) notes that the advantages of these developed commercial nodes lead to rapidly rising land values, which are indicative of urbanism in rural areas.…”
Section: The Role Of Rural Towns In Rural Developmentmentioning
confidence: 99%